Identification of the Aroma Compounds of Ocimum americanum as a Function of Growth Stages and their In Vitro Antioxidant and Anti-inflammatory Potential. Issue 2 (4th March 2022) - Rana, Lata; Tewari, Geeta; Pande, Chitra; Prakash, Om; Bisht, Mamta; Bhatt, Sunita; Kanyal, Bhawana; Rana, Krishna
Abstract: The present study investigated the variability in the content, composition, antioxidant and anti-inflammatory potential of the volatile oil constituents of aerial parts of Ocimum americanum Linn. collected at two stages from two sites of north Himalayas. The essential oils of O. americanum at vegetative and full blooming stages were isolated by using hydrodistillation technique and analysed by gas chromatography with flame ionization detection (GC/FID), GC-with mass spectrometry (GC/MS). The antioxidant potential was evaluated using 2, 2ʹ-diphenyl -1-picrylhydrazyl (DPPH) radical scavenging activity, Fe 2+ ferrozine test for iron-chelating and hydrogen peroxide scavenging activity methods while anti-inflammatory activity was assayed by measuring the protein denaturation capacity of oil samples. The oil content was recorded highest during the full blooming stage from Ct-2 collection. Out of 28-31 identified constituents, β-bisabolene (14.46-29.74%), ( E )-α-bisabolene (11.42-22.17%), methyl chavicol (11.28-17.83%), ( E )-β-ocimene (7.48-11.54%), 1, 8-cineole (3.29-17.40%), eugenol (1.27-10.42%) and germacrene D (1.92-8.39%) were the major constituents. The oil composition during full blooming stages was characterized by the abundant presence of sesquiterpenes (34.34-70.81%) while phenyl propanoids became the dominant class at vegetative stages (12.55-25.42%). EO's revealed good results of anti-inflammatory and antioxidant activity at both stages while more potent at full blooming stage.